English For Hospitality: Meningkatkan Layanan Wisata Berbasis Komunikasi Efektif Di Desa Wisata Belitar Seberang, Kabupaten Rejang Lebong - Eli Diana; Merry Rullyanti; Ahmad Syafran; Aget Pramana; Tasya Masela (Universitas Dehasen Bengkulu, 2026)
Village tourism activists play a direct role as the front line in providing experiences to tourists. Therefore, good communication skills are a crucial factor in creating a positive impression and increasing tourist satisfaction. Based on the results of a preliminary survey conducted by the Community Service team of the English Literature Study Program, FKIP, Dehasen University Bengkulu, it is known that Belitar Seberang Tourism Village has begun to receive foreign tourists, although the number is not yet significant. The survey results also show that most village tourism activists still have limitations in using spoken English. These limitations include difficulty in greeting tourists, explaining tourist attractions, and providing basic information related to tourist facilities and activities. This condition causes the interaction process to not run optimally and has the potential to reduce the quality of tourism services. In addition to language skills, effective and tourist-friendly communication patterns also need to be improved. The results of the activities show that the non-formal socialization and contextual learning approaches carried out directly at tourist sites are effective in improving basic English for Hospitality communication skills. Village tourism activists are able to use simple expressions to greet tourists, provide brief information about tourist attractions, and offer assistance with more confidence. These findings indicate that field-based learning is more easily accepted and applied by participants than formal training approaches.